Staff radiation dose and estimated risk in an interventional radiology department - Alkhorayef, M.; Al-Mohammed, H.I.; Mayhoub, Fareed H.; Sulieman, Abdelmoneim; Salah, Hassan; Yousef, M.; Alomair, Othman I.; Bradley, D.A. * (Elsevier, 2021)
In interventional radiology attendant staff can be exposed to significant doses from the radiation scattered from the patient, giving rise to heterogeneous energy distribution, exposure occurring over extended periods of time. Protection of staff is a prime concern, also including reducing the risk of carcinogenesis. With only limited published studies available, as in for instance in regard to lens opacifications, further evaluation of staff exposures and assessment of radiation protection techniques and measures are crucial. Present study has sought to evaluate staff radiation exposure in a radiology department that performs interventional procedures. Annual occupational exposures were obtained for 32 personnel (6 females and 26 males) in a radiology department at a tertiary hospital. Personal dose equivalent Hp (d) was measured in terms of Hp (0.07) (shallow dose) and Hp (10) (deep dose). The measurements were made over a period of two consecutive years, 2017 and 2018, use being made of TLD-100 thermoluminescent dosimeters. In units of mSv, the corresponding average annual dose equivalent and range for Hp (10) and Hp (0.07) were 4.6 ± 7.0 (0.1–25.5) and 5.1 ± 7.3 (0.1–25.5). Notably, 16% of staff received doses that were greater than the annual dose limit. Since Hp (10) offers a conservative evaluation of effective dose, evaluation of the working environment is necessary in seeking to ensure dose values remain below annual dose limits.